2000
DOI: 10.1115/1.1314379
|View full text |Cite
|
Sign up to set email alerts
|

Solar Chimney Cycle Analysis With System Loss and Solar Collector Performance

Abstract: An ideal air standard cycle analysis of the solar chimney power plant gives the limiting performance, ideal efficiencies and relationships between main variables. The present paper includes chimney friction, system, turbine and exit kinetic energy losses in the analysis. A simple model of the solar collector is used to include the coupling of the mass flow and temperature rise in the solar collector. The method is used to predict the performance and operating range of a large-scale plant. The solar chimney mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(72 citation statements)
references
References 4 publications
1
71
0
Order By: Relevance
“…In this article, the efficiency of the turbine generator is recommended by other researchers as 80% [27].…”
Section: Performance Analysis Of Solar Chimneymentioning
confidence: 99%
“…In this article, the efficiency of the turbine generator is recommended by other researchers as 80% [27].…”
Section: Performance Analysis Of Solar Chimneymentioning
confidence: 99%
“…The performance of solar chimney plants has been investigated by several researchers [1][2][3][4][5]. Among others, Serag-Eldin [6] has shown that, for a given collector area, the performance increases rapidly with increase of height of stack.…”
Section: Conventional Solar-chimney Plantmentioning
confidence: 99%
“…Gannon and Backstrom [76] developed an ideal air-standard cycle analysis to calculate all the thermodynamic variables depending on the chimney height, wall friction, additional losses, internal drag and area change. The developed analytical model showed good agreement with the experimental results of the small-scale plant built in Manzanares allowing it to be used reliably in the prediction of the output of a full-scale plant.…”
Section: Analytical and Simulation Studiesmentioning
confidence: 99%